Comparative Proteomics in Rice Seedlings to Characterize the Resistance to Cadmium Stress by High-Performance Liquid Chromatography – Tandem Mass Spectrometry (HPLC-MS/MS) with Isobaric Tag for Relative and Absolute Quantitation (iTRAQ). (23rd March 2020) - Liu, Sanxiong; Li, Yongchao; Liu, Licheng; Min, Jun; Liu, Wenqiang; Li, Xiaoxiang; Pan, Xiaowu; Lu, Xiangyang; Deng, Qiyun
Abstract: Cadmium (Cd) is a heavy metal used in industrial processes that impedes the growth of plants. Although intensive work has concentrated on the mechanism of rice under Cd stress, few studies compared the proteomic information on the mechanism between different cultivars. Different rice cultivars were screened and two cultivars, the japonica cultivar Bancanggengnuo (BCGN) and indica cultivar Yuzhenxiang (YZX) were selected to be the varieties for proteomic experiments. High-performance liquid chromatography – tandem mass spectrometry (HPLC-MS/MS) with an isobaric tag for relative and absolute quantitation (iTRAQ) was used to analyze the global protein profiles of these two cultivars. There were 109 and 209 differentially expressed proteins (DEPs) in the Cd treatment groups for BCGN and YZX respectively and 61 additional DEPs between cultivars after treatment. Pathway enrichment analysis showed that three pathways were altered in the cultivars, which affected photosynthesis and redox reactions. A total of 37 up- and 27 down-regulated proteins were identified in both cultivars exposed to Cd. The molecular regulatory network revealed that several proteins associated with carbohydrate metabolism, redox reaction and signal transduction were involved in and acted as the intersection point of disturbed metabolism. This is the first report on the comprehensive proteomic characterization of Cd-exposed leaf proteomes in rice. These findings may facilitate the unraveling molecular mechanism underlying Cd stress response in rice, and provide fundamental insights into the development of Cd-resistant rice cultivars. This work has explored the mechanism of Cd resistance at the protein level, which may be a novel target for improving the resistance of rice to this heavy metal.